Abacate (Persea americana Mill.) na alimentação de cabras: produção, composição e perfil de ácidos graxos no leite e parâmetros ruminais - Pastor López, Francisco Javier [UNESP] (2015)
The fastest strategy that alters Milk fatty acid profile in order to benefit consumer health is to improve the level of conjugated linoleic acid (CLA) by supplementing animal diets with vegetable oils. This research aimed to evaluate goat diets supplemented with avocado addition using a fruit polp with 16% of ether extract (EE) in dry matter (DM) and commercial oil with 8% EE in DM on: intake and milk production, chemical composition and fatty acid profile. There were used six Anglo Nubian lactating goats, distributed in two balanced 3 x 3 latin squares. Pulp diet reduced and oil diet improved DM intake in relation to control (3% EE), and the nutrients followed the same tendency, except for EE, that was more consumed in pulp and oil diets. The content of milk total solids and fat were higher in oil diet in relation to control, and did not differ from pulp diet, the other constituents and the milk production were not influenced by diets. In relation to fatty acids, it was observed reduction in short chain fatty acids in milk from goats supplemented with lipid sources in relation to control and increase on CLA level in 56,88 and 66,10/% in treatments with pulp and oil respectively. The supplementation with unsaturated fatty acids by avocado oil and pulp increases CLA concentration and decreases short chain fatty acids, improving milk nutraceutical properties, what can benefit consumer health.